1987
DOI: 10.1530/jrf.0.0790457
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a luteolytic dose of oestradiol benzoate on uterine oxytocin receptor concentrations, phosphoinositide turnover and prostaglandin F-2  secretion in sheep

Abstract: Administration of oestradiol-17 beta benzoate on Days 9 and 10 of the oestrous cycle resulted in episodic secretion of PGF-2 alpha (as indicated by elevated circulating concentrations of 13,14-dihydro-15-ketoprostaglandin F-2 alpha) and a decline in circulating progesterone. Release of PGF-2 alpha began 35 +/- 3 h after first injection of oestrogen and progesterone concentrations declined from 42 +/- 3 h. Secretion of oxytocin, which was first observed 26 +/- 3 h after oestrogen treatment, preceded secretion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
61
1
7

Year Published

1990
1990
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(77 citation statements)
references
References 7 publications
8
61
1
7
Order By: Relevance
“…Maximum concentrations occur during oestrus, and are lower, relatively, 4 to 5 days earlier or later (Roberts et al, 1976;Sheldrick and Flint, 1985). During oestrus, plasma concentrations of progesterone are minimal whereas oestradiol concentrations are maximal, suggesting that oxytocin receptor synthesis is inhibited by progesterone (Hunter et al, 1989;Vallet et al, 1990) and increased by oestradiol (Hixon and Flint, 1987).…”
Section: Introductionmentioning
confidence: 95%
“…Maximum concentrations occur during oestrus, and are lower, relatively, 4 to 5 days earlier or later (Roberts et al, 1976;Sheldrick and Flint, 1985). During oestrus, plasma concentrations of progesterone are minimal whereas oestradiol concentrations are maximal, suggesting that oxytocin receptor synthesis is inhibited by progesterone (Hunter et al, 1989;Vallet et al, 1990) and increased by oestradiol (Hixon and Flint, 1987).…”
Section: Introductionmentioning
confidence: 95%
“…However, it remains unclear whether the inhalation of cigarette smoke directly enhances the expression of OTR mRNA in the myometrium. Since OTR levels are known to be upregulated through progesterone regression, which occurs during luteolysis in the ewe (Hixon & Flint 1987, Zhang et al 1992, the increased expression of OTR mRNA in the pregnant rat myometrium, in the smoking group, may be caused indirectly through progesterone regression via luteolysis. Thus, inhalation of cigarette smoke may damage the function of the corpus luteum in the pregnant rat.…”
Section: Discussionmentioning
confidence: 99%
“…This uncertainty is based upon the findings that progesterone decreases the levels of uterine OTR mRNA and protein in pregnant rats (Soloff et al 1983), and estrogen increases the levels of OTR in the rat uterus and in human-cultured myometrial cells (Soloff 1975, Adachi & Oku 1995. Additionally, it has been reported that OTR levels are upregulated through progesterone regression, which occurs during luteolysis in the ewe (Hixon & Flint 1987, Zhang et al 1992. Therefore, the increased expression of OTR mRNA in the pregnant rat myometrium in the smoking group may be caused indirectly through progesterone regression via luteolysis.…”
Section: Introductionmentioning
confidence: 99%
“…Oxytocin then up-regulates an enzyme, cyclooxygenase-2 (COX-2), which converts arachidonic acid to PGG2 and PGH2, precursors for PGE2 and PGF2α, respectively [41][42][43], and subsequently induces pulsatile PGF2α production during luteolysis [44,45]. Estrogen affects the oxytocin-induced PGF 2α production presumably through the up-regulation of the OTR receptor [46,47]. Estrogen receptor (ER) is up-regulated before luteolysis, which coincides with an increase in OTR [39,48,49].…”
Section: Biological Properties Of Ifnτ τ τ τmentioning
confidence: 99%